2015
DOI: 10.1016/j.vaccine.2015.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Text message reminders for timely routine MMR vaccination: A randomized controlled trial

Abstract: Objective Measles–mumps–rubella (MMR) vaccination is important for preventing disease outbreaks, yet pockets of under-vaccination persist. Text message reminders have been employed successfully for other pediatric vaccines, but studies examining their use for MMR vaccination are limited. This study assessed the impact of text message reminders on timely MMR vaccination. Study design Parents (n = 2054) of 9.5–10.5-month-old children from four urban academically-affiliated pediatric clinics were randomized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 20 publications
3
53
0
Order By: Relevance
“…It found a non-significant uptake difference after 2 weeks. An RCT undertaken in an urban, low-income minority ethnic population in the USA randomised participants to receive text-message reminders to schedule an appointment and/or reminders of the appointment details, or usual care to increase MMR vaccine uptake at 13 months 77. There was no difference in uptake between the arms, except in children who did not have a vaccination appointment booked and who received scheduling and appointment reminders.…”
Section: Resultsmentioning
confidence: 99%
“…It found a non-significant uptake difference after 2 weeks. An RCT undertaken in an urban, low-income minority ethnic population in the USA randomised participants to receive text-message reminders to schedule an appointment and/or reminders of the appointment details, or usual care to increase MMR vaccine uptake at 13 months 77. There was no difference in uptake between the arms, except in children who did not have a vaccination appointment booked and who received scheduling and appointment reminders.…”
Section: Resultsmentioning
confidence: 99%
“…Vaccine reminders with SMS technology have yielded promising results when used in high-income countries. Studies have shown increased compliance with vaccination schedules in travelers receiving the hepatitis A and B vaccine series [24] , pediatric patients receiving influenza [25] , [26] and post shortage Haemophilus influenza B [27] , adolescent patients receiving MCV4/Tdap [27] and human papillomavirus [28] immunizations, and children receiving their primary immunization series [29] and MMR vaccination [30] . Preliminary studies are promising and suggest that parents may even prefer text message reminders over other forms of communication [31] , [32] .…”
Section: Discussionmentioning
confidence: 99%
“…[54][55][56][57] Systematic reviews have indicated that text messaging can be effective in facilitating short-term behaviour and medication adherence in particular. 51 However, the quality of studies is often poor, with research frequently conducted with population samples that may not be representative, and with limited understanding of long-term effectiveness and patient satisfaction.…”
Section: Text Messaging and E-mailmentioning
confidence: 99%